1996
DOI: 10.1002/pro.5560050615
|View full text |Cite
|
Sign up to set email alerts
|

Invariant glycines and prolines flanking in loops the strand β2 of various (α/β)8‐barrel enzymes: A hidden homology?

Abstract: The question of parallel (a/&barrel fold evolution remains unclear, owing mainly to the lack of sequence homology throughout the amino acid sequences of (a/P),-barrel enzymes. The "classical" approaches used in the search for homologies among (cu/@),-barrels (e.g., production of structurally based alignments) have yielded alignments perfect from the structural point of view, but the approaches have been unable to reveal the homologies. These are proposed to be "hidden" in (a/P),-barrel enzymes. The term "hidde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 76 publications
(50 reference statements)
1
1
0
Order By: Relevance
“…Altogether, the conserved sequential distribution of patterns suggests that all members of the subset of glycogen-associated PP1 regulatory subunits studied here share a common fold: like hGM, they may possess an~a0b! 8 -barrel-like fold very often encountered in starch and polysaccharide-related enzymes~Farber & Petsko, 1990;Jespersen et al, 1993;Janecek, 1996!. This fold has been shown in this work to be consistent with PP1C anchoring and glycogen interaction, both processes being predominantly controlled by hydrophobic forces deriving from F660V64 and V1480 F1530V157~hGM numbering!, respectively.…”
Section: Consistency Of the Model With Data Related To The Glycogen-isupporting
confidence: 80%
“…Altogether, the conserved sequential distribution of patterns suggests that all members of the subset of glycogen-associated PP1 regulatory subunits studied here share a common fold: like hGM, they may possess an~a0b! 8 -barrel-like fold very often encountered in starch and polysaccharide-related enzymes~Farber & Petsko, 1990;Jespersen et al, 1993;Janecek, 1996!. This fold has been shown in this work to be consistent with PP1C anchoring and glycogen interaction, both processes being predominantly controlled by hydrophobic forces deriving from F660V64 and V1480 F1530V157~hGM numbering!, respectively.…”
Section: Consistency Of the Model With Data Related To The Glycogen-isupporting
confidence: 80%
“…Sequence-alignment comparisons of various AKRs revealed that the amino-acid sequences forming the barrel are well conserved compared with those forming the loop regions. The conserved regions seemingly maintain the architecture of the barrel, while residues belonging to the loop regions discriminate between several structurally related substrates and act as specificity determinants (Matsuura et al, 1998;Janecek, 1996;Jez et al, 1997). The reactions catalyzed by AKR enzymes follow an ordered bi-bi mechanism in which the coenzyme binds first and leaves last.…”
Section: Introductionmentioning
confidence: 99%